Consideration of peak cut method by air conditioning equipment corresponding to demand for contract power reduction—Application of thermal radiative cooling/heating system - Akihiro Satake; Junpei Jike; Yasunori Mitani (Energy Reports, 2020)
Electricity demand leveling has actively been pursued in order to reduce power supply costs and reduce carbon dioxide emissions. In addition, large-scale customers have attracted great interest because of the expectation of contract power reduction. Focusing on the air conditioning equipment whose seasonal factors greatly change their demand, the peak cut operation has been considered for customers who have a large proportion of the load on the air conditioning equipment. The thermal radiative cooling/heating system is applied as the air conditioning equipment, and power control is performed according to the electricity demand of the customer. The comfort is evaluated by simulating the change in room temperature at that time. As a result, it is shown that the proposed demand response method can perform peak cut operation while ensuring comfort.